Getting the Most Out Of Makerspaces To Build Unmanned Aerial Vehicles - Don Rauf
The makerspace movement is as nascent and revolutionary as the technology behind unmanned aerial vehicles (UAVs), and this volume introduces readers to both fascinating worlds. UAVs are no longer science fiction. Though their surveillance capabilities are controversial, theyre also being used for more practical purposes. This volume teaches young people how members of the maker movement are producing their own UAVs for productive purposes. Readers learn just what makerspaces are and where to find one in their own community, hopefully piquing their interest in engineering careers.